Vermiremediation: Analysis of contaminated diesel in soil using Eisenia fetida and ZnO nanoparticles with cow dung - Surendrakumar, Radhakrishnan; Idhayadhulla, Akbar; Ahamed, Anis; Alodaini, Hissah Abdulrahman; Gurusamy, Raman (Frontiers in Environmental Science, 2022)
Small livestock is often raised on cow dung, which is a good source of manure to enhance soil quality in many countries. By reducing diesel contamination in soil through the vermicomposting of cow dung and nanoparticles of ZnO, this research aims to improve vermicomposting. We report the synthesis of ZnO (NPs) with cow dung. Zinc oxide ions may be easily reduced into ZnO nanoparticles using a cow-dung powder. To increase the stability of Eisenia fetida, nanoparticles of ZnO were mixed with cow dung in order to improve vermiremediation of natural nanomaterials. This nanoparticle was characterized by FT-IR, SEM, and TEM. The impure soils were examined for the total diesel level for 70 days using gas chromatography. Observations showed that the soil samples without the earthworms had a higher concentration of diesel than the equivalent samples with the earthworms. Diesel was reduced by almost 50% after 70 days. Diesel concentrations were significantly higher during sampling time than they were later in soil contaminated with E. fetida.